The double sampling and the EWMA charts based on the sample variances - Machado, Marcela A. G.; Costa, Antonio F. B. [UNESP] (Elsevier B.V., 2008)
We propose a new statistic to control the covariance matrix of bivariate processes. This new statistic is based on the sample variances of the two quality characteristics, in short VMAX statistic. The points plotted on the chart correspond to the maximum of the values of these two variances. The reasons to consider the VMAX statistic instead of the generalized variance vertical bar S vertical bar is its faster detection of process changes and its better diagnostic feature; that is, with the VMAX statistic it is easier to identify the out-of-control variable. We study the double sampling (DS) and the exponentially weighted moving average (EWMA) charts based on the VMAX statistic. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: control charts; covariance matrix; double sampling; EWMA; generalized variance